EDUCATION AS A MEANS OF AFFIRMING DEMOCRACY VALUES IN JOHN DEWEY’S PRAGMATISM: MODERN PERSPECTIVE - Synytsia, Andrii (Journal of Education Culture and Society, 2020)
Aim. The aim of the research is to analyse the capabilities of Dewey’s pragmatism in the philosophy of education as a medium for affirming today’s values of democracy. Methods. The article is based on a conceptually extended literature review. Such philosophical methods as hermeneutics (to take into account the socio-cultural context in the process of investigating the content of primary sources), interpretation (to study the basic theoretical foundations of the educational process and to explain their practical value) and comparative analysis (to identify similarities or differences between different ideas and conceptions) are applied. Results. The research identified the philosophical dimension of education, making it possible to understand the nature of learning in pragmatism. An investigation is pursued into what role the activity of the subject plays in the learning process, how the importance of freedom is substantiated in communication, and what place in the face of contemporary civilisational challenges has experience as a medium of true knowledge for becoming the ideals of a democratic society. Conclusion. The methodology of pragmatism makes it possible to resolve contradictions in education. The theoretical and practical principles of pragmatism that were substantiated by John Dewey contribute to the formation of an active life position of students, the free and constructive communication between all participants in learning, and the promotion of the ideals of a democratic society. They create an environment for the formation of genuine experience and the development of critical thinking skills as reliable means of protecting against misinformation or the spread of false values and the precondition for the advancement of humanistic values. Key words: philosophy of education, democratic values, Dewey’s pragmatism